Blade design for horizontal axis wind turbine: 3D model. - Albadan Molano, David Esteban; Salamanca Céspedes, Jorge Enrique (Visión electrónica, 2019)
Wind energy is one of the best important sources of renewable energy and an excellent alternative for the transition to sustainable energy that the planet earth needs. The wind energy is contained in the air particles in movement, forming kinetic energy. This energy could be transformed into another type of energy such as electricity, through the use of wind turbines. It is known that horizontal axis wind turbines are more efficient energetically, the power output of a horizontal axis wind turbine depends of it aerodynamic performance; therefore, the correct geometric design of the propeller is essential for an optimum wind turbine. This article analyzes the most relevant aspects in the design of a wind propeller, using MATLAB® software to illustrate its behavior, suggests an ideal airfoil for wind applications to use in the 3D modeling of the blades using the computer assisted design, this blades has been built with a 3D printer.